2000
DOI: 10.1002/(sici)1099-0682(200002)2000:2<299::aid-ejic299>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Chelate Complexes of 2-Alkylphenylphosphanylphenolates: Synthesis, Structural Investigation and Use in Ethylene Polymerization

Abstract: 2‐Diphenylphosphanyl‐ and 2‐alkylphenylphosphanyl‐4‐methylphenols 1 or their silyl ethers 2 and equimolar amounts of nickelocene react in benzene preferably to give orange‐brown diamagnetic cyclopentadienylnickel chelate complexes [η‐CpNi(P∩O)] (3). Addition of a second equivalent of 1 or 2 affords (RR) and (SS) diastereoisomers of cis‐bis(P∩O‐chelates) 4a–c (R = Ph, Me, iPr) or the unsymmetrical cis‐bis(P∩O‐chelate) 5, whereas with bulkier substituted derivatives 1d or 2d (R = tBu) the second step is hindered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Here we report a novel class of Ni-based SHOP catalysts, the preparation of which is shown in Scheme where the reaction of Ni­(cod) 2 and o -bis­(aryl)­phosphinophenol 1a – 1i gave neutral σ, π-cyclooct-4-enyl Ni­(II) complexes 2a – 2i almost quantitatively . We found that the complexes can copolymerize ethylene and alkyl acrylates with high activity to give highly linear copolymers with high molecular weight (Scheme ).…”
mentioning
confidence: 96%
“…Here we report a novel class of Ni-based SHOP catalysts, the preparation of which is shown in Scheme where the reaction of Ni­(cod) 2 and o -bis­(aryl)­phosphinophenol 1a – 1i gave neutral σ, π-cyclooct-4-enyl Ni­(II) complexes 2a – 2i almost quantitatively . We found that the complexes can copolymerize ethylene and alkyl acrylates with high activity to give highly linear copolymers with high molecular weight (Scheme ).…”
mentioning
confidence: 96%
“…[77,79] The silyl ethers can also be used for O-lithiation, O-acylation, [97b] reactions with ClER n reagents, with transition metal halides and the preparation of (P,O)-nickel ethylene polymerization catalysts. [98] The o-lithio-phenolates and -naphtholates 26 OM (M=Li or Na; R n = H and 5,6-C 4 H 4 ) were also applied to stereospezific syntheses of P-asymmetric o-hydroxyarylphosphanes, using the Jugé-Stephan route. Reaction in THF (À 20 °C to rt) with the (2S,4R,5S)-(-)-1,3,2-oxazaphospholidine 32, obtained from PhP(NEt 2 ) 2 , (+)-ephedrine and BH 3 •THF, [99] provides the PÀ O ring-opening product (R P )-33 with retention of configuration (Scheme 9).…”
Section: O-hydroxyarylphosphanes Via Cà P Bond Formation With O-oc-di...mentioning
confidence: 99%
“…By reaction with MeOH in the absence of traces of acids and moisture (best in the presence of Et 3 N to avoid side products by H + ‐catalyzed Arbuzov reaction) the NR 2 groups of 29 are replaced by OMe groups and allow reduction by LiAlH 4 to PH‐functional o ‐phosphanylphenols [77,79] . The silyl ethers can also be used for O‐lithiation, O‐acylation, [97b] reactions with ClER n reagents, with transition metal halides and the preparation of ( P , O )‐nickel ethylene polymerization catalysts [98] …”
Section: Routes To 2‐hydroxyarylphosphanesmentioning
confidence: 99%